LCORL and STC2 Variants Increase Body Size and Growth Rate in Cattle and Other Animals - Bai, Fengting; Cai, Yudong; Qi, Min; Liang, Chen; Pan, Linqian; Liu, Yayi; Feng, Yanshuai; Cao, Xuesha; Yang, Qimeng; Ren, Gang; Jiao, Shaohua; Gao, Siqi; et al. (Genomics, proteomics & bioinformatics, 2025)
Natural variants can significantly improve growth traits in livestock and serve as safe targets for gene editing, thus being applied in animal molecular designed breeding. However, such safe and large-effect mutations are severely lacking. Using ancestral recombination graphs, we investigated recent selection signatures in beef cattle breeds, pinpointing sweep-driving variants in the LCORL and STC2 loci with notable effects on body size and growth rate. The ACT-to-A frameshift mutation in LCORL occurs mainly in central-European cattle, and stimulates growth. Remarkably, convergent truncating mutations were also found in commercial breeds of sheep, goats, pigs, horses, dogs, rabbits, and chickens. In STC2 gene, we identified a missense mutation (A60P) located within the conserved region across vertebrates. We validated the two natural mutations in gene-edited mouse models, where both variants in homozygous carriers significantly increase the average weight by 11%. Our findings provide insights into a seemingly recurring gene target of body size enhancing truncating mutations across domesticated species, and offer valuable targets for gene editing-based breeding in animals.